Competitividad en las empresas constructoras de vivienda en Michoacán - Ramírez Herrejón, Nora Janette (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
The objective of this research is to analyze to what extent business practices such as Innovation, Technology and Intellectual Capital affect the competitiveness of housing construction companies in Michoacán. This research is quantitative, cross-sectional and descriptive. 105 questionnaires with an ordinal Likert scale were applied to the managers and directors of housing construction companies registered with the Ministry of Communications and Transportation (SCOP) of Michoacán. To process the data, the second-generation statistical technique “Structural Equation Modeling” Partial Least Squares (PLS-SEM) is used, widely used by researchers in the areas of social sciences, due to its efficiency in the reduced handling of data. data. The results obtained confirm the hypothesis that business practices on Innovation, Technology and Intellectual Capital positively impact the Competitiveness of housing construction companies in Michoacán.

El objetivo de esta investigación es analizar en qué medida las prácticas empresariales como la Innovación, la Tecnología y el Capital Intelectual inciden en la competitividad de las empresas constructoras de vivienda en Michoacán. Esta investigación es de tipo cuantitativo de corte transversal y descriptiva. Se aplicaron 105 cuestionarios con escala ordinal Likert, a los gerentes y directores de empresas constructoras de vivienda registradas en la Secretaría de Comunicaciones y Transportes (SCOP) de Michoacán. Para el tratamiento de los datos se utiliza la técnica estadística de segunda generación “Modelización de Ecuaciones Estructurales” Partial Least Squares (PLS-SEM), ampliamente utilizada por investigadores en las áreas de las ciencias sociales, debido a su eficiencia en el manejo reducido de datos. Los resultados obtenidos confirman la hipótesis de que las prácticas empresariales sobre la Innovación, la Tecnología y el Capital Intelectual impactan de manera positiva en la Competitividad de las empresas constructoras de vivienda en Michoacán.
Facultad de Contaduría y Ciencias Administrativas. Doctorado en Administración
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18526; info:eu-repo/classification/cti/5; FCCA-D-2024-0278; Competitividad; Innovación; Tecnología